Effect of Pretreatment with Coenzyme Q10 and DHEA before ART in Patients with Diminished Ovarian Reserve (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Objective (s): Aim of this study was to explore the efficacy of pretreatment with a combination of coenzyme Q10 (CoQ10) and dehydroepiandrosterone (DHEA) in comparison to that of DHEA alone before IVF-ICSI cycles in patients with diminished ovarian reserve. Methods: This retrospective case control study was conducted in Infertility Care and Research Center (ICRC) Ltd Dhaka, Bangladesh between January 2018 and December 2023. One hundred and forty (140) patients who had AMH level